Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1016/s0896-6273(00)80526-7
|View full text |Cite
|
Sign up to set email alerts
|

Cue-Invariant Activation in Object-Related Areas of the Human Occipital Lobe

Abstract: The extent to which primary visual cues such as motion or luminance are segregated in different cortical areas is a subject of controversy. To address this issue, we examined cortical activation in the human occipital lobe using functional magnetic resonance imaging (fMRI) while subjects performed a fixed visual task, object recognition, using three different primary visual cues: motion, texture, or luminance contrast. In the first experiment, a region located on the lateral aspect of the occipital lobe (LO co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
215
0
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 368 publications
(262 citation statements)
references
References 35 publications
36
215
0
5
Order By: Relevance
“…The three ROIs (V1, MTϩ, and LOC) showed significant increases in activity in response to motion stimuli (velocity-scrambled or SFM) compared with the stationary stimuli, with MTϩ showing the largest signal increase. In response to the SFM shapes, activity increased significantly in the LOC in comparison with the velocity-scrambled control, consistent with other studies showing that the LOC integrates multiple shape cues (21,22). By contrast, both V1 and MTϩ showed significant reductions in activity during object perception (Fig.…”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…The three ROIs (V1, MTϩ, and LOC) showed significant increases in activity in response to motion stimuli (velocity-scrambled or SFM) compared with the stationary stimuli, with MTϩ showing the largest signal increase. In response to the SFM shapes, activity increased significantly in the LOC in comparison with the velocity-scrambled control, consistent with other studies showing that the LOC integrates multiple shape cues (21,22). By contrast, both V1 and MTϩ showed significant reductions in activity during object perception (Fig.…”
Section: Methodssupporting
confidence: 90%
“…Activity in the LOC increased in response to the shape stimuli, with the 2D shapes activating the LOC significantly more than the random lines, and the 3D shapes activating the LOC more than the 2D shapes, consistent with previous findings (9,10,(21)(22)(23). By contrast, activity in V1 showed an opposite pattern: significant reductions in response to the 2D shapes compared with the random lines and significantly less activity for 3D than 2D shapes (Fig.…”
Section: Subjects and Proceduresupporting
confidence: 90%
“…Indeed, in Kristjánsson et al's study, there was evidence for repetition suppression on target-repeated trials in inferior temporal areas as well as in fronto-parietal areas. Inferior temporal areas are known to process object-related information such as color and shape (see, e.g., Grill-Spector, Kushnir, Edelman, Itzchak, & Malach, 1998;Grill-Spector & Malach, 2001), whereas the fronto-parietal network is believed to control spatial attention (Kastner & Ungerleider, 2001;LaBar, Gitelman, Parrish, & Mesulam, 1999). Finally, eye movement data on three-item oddball displays like the ones used here also showed that participants were actually relatively bad at fixating the target when the target on the current trial differed in color identity from that on the previous trial (Becker, 2008;Caddigan & Lleras, 2010).…”
Section: Discussionmentioning
confidence: 54%
“…Our previous source-imaging studies using frequency tagging have suggested that the LOC is tuned for the configuration of a small figure on a larger background (Appelbaum et al, 2010) and that LOC responses to figures are largely cue-invariant (Appelbaum et al, 2006(Appelbaum et al, , 2012. Cue-invariance in LOC has also been found with fMRI (Grill-Spector et al, 1998).…”
Section: Tuning For Shapementioning
confidence: 80%
“…In fMRI studies the LOC is activated more by intact than by scrambled images of objects (Grill-Spector et al, 1998;Kourtzi and Kanwisher, 2000;Malach et al, 1995). Moreover, the LOC contains a representation of the perceived shape of objects (Kourtzi and Kanwisher, 2001;Vinberg and Grill-Spector, 2008).…”
Section: Tuning For Shapementioning
confidence: 99%